Linking information on unemployment benefit sanctions from different datasets about welfare receipt: Proceedings and research potential - Julia Schmidtke (Journal for Labour Market Research, 2023)
Most studies on benefit sanctions within the German welfare system rely on established datasets about welfare receipt. This paper analyzes how using a dataset from the operational system of the German Federal Employment Agency for processing welfare claims can contribute to further research on benefit sanctions. For this purpose, I use a random sample of welfare recipients with at least one sanction between 2016 and 2018. First, this allows the detailed analysis of time lags between different steps in the sanction process. Second, linking this dataset with established datasets allows the identification of imposed sanctions for which sanction periods could not be (fully) implemented. This is largely explained by individuals leaving the welfare system between sanction events and sanction periods, e.g., by taking up employment. Third, the paper shows differences in benefit cuts across subgroups. This opens up paths for future research.
Keywords: C81; J65; I38; J68; 330; Unemployment benefts; Beneft sanction; Labor market policies